2012
DOI: 10.3749/canmin.50.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Te-RICH CANFIELDITE, Ag8Sn(S,Te)6, FROM THE LENGENBACH QUARRY, BINNTAL, CANTON VALAIS, SWITZERLAND: OCCURRENCE, DESCRIPTION AND CRYSTAL STRUCTURE

Abstract: In order to evaluate the effects of Te-for-S substitution in the minerals of the argyrodite group, the crystal structure and chemical composition of a crystal of Te-rich canfieldite from the Lengenbach quarry, Binntal, Switzerland, was investigated. The unit-cell parameters are a 11.0003(6) Å and V 1331.1(1) Å 3 . The structure was solved and refined in the space group F43m to R 1 = 0.0308 for 194 independent reflections and 21 parameters. Quantitative analysis led to the chemical formula Ag 8.05 (Sn 1.03 Ge 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
10
2
Order By: Relevance
“…Intensity integration, standard Lorentz polarisation and absorption correction were performed with the Crysalis (Oxford Diffraction, 2006) software package. Given the similarities in the unit-cell, cubic symmetry and reflections conditions between the examined crystal and Te-rich canfieldite (Bindi et al , 2012), the crystal-structure refinement was carried out starting with the atom coordinates reported for the F 3 m structure of Te-rich canfieldite. The full-matrix least-squares program SHELXL-97 (Sheldrick, 2008) was used for the refinement of the structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity integration, standard Lorentz polarisation and absorption correction were performed with the Crysalis (Oxford Diffraction, 2006) software package. Given the similarities in the unit-cell, cubic symmetry and reflections conditions between the examined crystal and Te-rich canfieldite (Bindi et al , 2012), the crystal-structure refinement was carried out starting with the atom coordinates reported for the F 3 m structure of Te-rich canfieldite. The full-matrix least-squares program SHELXL-97 (Sheldrick, 2008) was used for the refinement of the structure.…”
Section: Methodsmentioning
confidence: 99%
“…Revelstoke, Canada (Harris and Owens, 1971), Nakatatsu mine, Japan (Marioko, 1981), Roşia Montană deposit, Romania (Popescu and Neacşu, 2011), Cirotan mine, Indonesia (Milési et al , 1994), Panasqueira deposit, Portugal (Dykqs, 1985) and Lengenbach quarry, Binntal, Switzerland (Bindi et al , 2012). From the structural point of view, Bindi et al (2012) showed that Te does not occupy specific positions in the canfieldite structure, but it exhibits a disorder among the three available anion positions of the cubic F 3 m structure. Although a very similar structural response is expected for the Se-for-S substitution, it is of interest to verify such a behaviour, even though Se-bearing varieties of canfieldite have been reported rarely, and then only from occurrences in the ex USSR (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang (1978), argyrodite and canfieldite are isostructural (space group Pna2 1 or Pnam), and a solid solution exists between these two minerals. The crystal structure of argyrodite has been published by Eulenberger (1977) and that of a tellurian variant of canfieldite has been reported by Bindi et al (2012). Several structural studies on synthetic argyrodite-type compounds have been reported, Projection of the crystal structure of dervillite.…”
Section: Argyrodite-canfieldite Seriesmentioning
confidence: 99%
“…In the course of this research project (i.e. Biagioni et al , 2016; Bindi et al , 2012a,b, 2015a,b), we examined a sample from the Hemlo gold deposit, Marathon, Ontario, Canada (Harris, 1989), belonging to the mineralogical collections of the Museo di Storia Naturale of the University of Florence. The sample consists of tiny criddleite grains associated closely with aurostibite, stibarsen and native gold in a calcite matrix.…”
Section: Introductionmentioning
confidence: 99%